2016
DOI: 10.1038/srep32114
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Characterization of Nucleoplasmin/Histone Complexes Reveals Chaperone Versatility

Abstract: Nucleoplasmin (NP) is an abundant histone chaperone in vertebrate oocytes and embryos involved in storing and releasing maternal histones to establish and maintain the zygotic epigenome. NP has been considered a H2A–H2B histone chaperone, and recently it has been shown that it can also interact with H3-H4. However, its interaction with different types of histones has not been quantitatively studied so far. We show here that NP binds H2A–H2B, H3-H4 and linker histones with Kd values in the subnanomolar range, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 66 publications
4
20
0
Order By: Relevance
“…The stoichiometry of this complex was 1:1 tail:H3/H4 dimer (Supplementary Fig. 7c ), and is also consistent with the recently reported binding affinity and stoichiometry of Npm to H3/H4 27 .…”
Section: Resultssupporting
confidence: 91%
“…The stoichiometry of this complex was 1:1 tail:H3/H4 dimer (Supplementary Fig. 7c ), and is also consistent with the recently reported binding affinity and stoichiometry of Npm to H3/H4 27 .…”
Section: Resultssupporting
confidence: 91%
“…As previously demonstrated, npm2b functions as a histone chaperone to decondense sperm DNA as well as reorganize chromatin, thus, it has also been suggested to contribute to ZGA as well. [ 5 , 11 , 34 , 39 ] Npm2b is thought to be activated by various post-translational modifications and homo-pentamerisation [ 40 ], and subsequently interacts with chromatin by exchanging sperm-specific basic proteins with histones via its core domain and acidic tracts A1, A2 and A3 [ 32 , 36 , 38 , 41 44 ]. We found that most of the investigated Npm2a proteins possess acidic tract A1 while some have a shortened A2, in contrast to Npm2b proteins which have a long A2 and mostly lack A1.…”
Section: Resultsmentioning
confidence: 99%
“…NPM-fold histone chaperones also oligomerize, forming pentameric rings 61,62 (FIG. 3E) that are capable of binding multiple copies of various histone subtypes (TABLE 1) and promote tetrasome assembly 63,64 .…”
Section: Mechanistic Insights Into Chaperoning Histonesmentioning
confidence: 99%